Influência da taxa de resfriamento na microestrutura da fase quasicristalina na liga Al65Cu35-xFex com baixo teor de Fe solidificada fora do equilíbrio - Piedade, Luiz Alberto Silva da (2017)
Quasicrystals are materials that have unusual characteristics, they can not be described as crystalline, for not having long-range order, or as amorphous, have medium-range structure. Some Al-Cu-Fe family alloys presents quasicrystalline phases when have rapidly solidification. In order to obtain this alloy, ingots of the Al65Cu35-xFex family were casted with x=6 (atomic), initially in a standard mold with solidification equilibrium. To provide samples with different cooling rates, the alloy was cast in a stepped mold, containing six different steps, resulting in samples out of equilibrium state (rapidly solidification). For the analysis of the cooling curves, the CACC-TA technique was used, with cooling rates varying from170 to 540°C / s, which were obtained by dT/dt. Analyzes by optical microscopy, scanning electron microscopy (SEM), dispersive energy spectrometry (EDS), show microstructure with faceted dendrites, lamellar interdendritic formations and pentagonal precipitates (IQC). The Vickers microhardness ranged from 4.09 to 7.22 GPa and the X-ray diffraction (XRD) proved by characteristic diffractograms the icosahedral quasicrystalline phase formation.